Development of Sustainable Development Goals (SDGs) Education Management Based on Village Funds In Batang District - Turno, Turno; Fakhruddin, Fakhruddin; Sutarto, Joko; Asrori, Asrori (Universitas Negeri Semarang, 2024)
Departing from the initial conditions (Factual) Management of Sustainable Development Goals (SDGs) Education, How to manage Sustainable Development Goals (SDGs) Education Village Fund-based, How to management develop Sustainable Development Goals (SDGs) Education Village Fund-based and what is a feasible and final model for the development of Sustainable Development Goals (SDGs) education management based on Village Funds. The purpose of this study: 1) Analyzing the management of Sustainable Development Goals (SDGs) of Village Fund -Based Education which has been implemented in Batang Regency, 2) Designing Sustainable Development Goals (SDGS) Management of Village Fund -Based Education which is ideal and in accordance with regulations in Batang Regency, 3) found the validity of the Sustainable Development Goals (SDGS) management model of education developed in villages in Batang Regency, 4) Analyzing the effectiveness of the Sustainable Development Goals (SDGs) education management model developed in Batang Regency. The method used in this research is the R & D (Research and Development) approach. Three stages of Management development were developed: (1) Study guides, (2) development, and (3) development validation/testing stage. The initial findings of this research are: 1) Management of Sustainable Development Goals (SDGs) education Village Fund-based is still conventional, 2) Expert validation has resulted in the development of Village Fund-based Sustainable Development Goals (SDGs) education management, 3) A feasible and final model for the development of Sustainable Development Goals (SDGs) education management based on Village Funds in Batang Regency